2019
DOI: 10.3389/fpsyg.2019.00075
|View full text |Cite
|
Sign up to set email alerts
|

‘I Just Stopped Going’: A Mixed Methods Investigation Into Types of Therapy Dropout in Adolescents With Depression

Abstract: What does it mean to ‘drop out’ of therapy? Many definitions of ‘dropout’ have been proposed, but the most widely accepted is the client ending treatment without agreement of their therapist. However, this is in some ways an external criterion that does not take into account the client’s experience of therapy, or reasons for ending it prematurely. This study aimed to identify whether there were more meaningful categories of dropout than the existing dropout definition, and to test whether this refined categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 59 publications
6
74
3
1
Order By: Relevance
“…Further, existing research suggests the most common reason for non-mutual treatment endings in YP therapeutic settings was a therapeutic relationship disconnect (Carter, 1995 ; Garcia and Weisz, 2002 ). Although the current findings show significant associations between meaningful change and mutual agreement to end treatment, a recent study found no significant evidence linking YP depressive symptoms to mutual agreement on treatment ending (O'Keeffe et al, 2019b ). This inconsistency may warrant further investigations if we are to generalize findings across symptom type, treatment type, and the level of impact the psychosocial difficulties may have on the YP and their families.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Further, existing research suggests the most common reason for non-mutual treatment endings in YP therapeutic settings was a therapeutic relationship disconnect (Carter, 1995 ; Garcia and Weisz, 2002 ). Although the current findings show significant associations between meaningful change and mutual agreement to end treatment, a recent study found no significant evidence linking YP depressive symptoms to mutual agreement on treatment ending (O'Keeffe et al, 2019b ). This inconsistency may warrant further investigations if we are to generalize findings across symptom type, treatment type, and the level of impact the psychosocial difficulties may have on the YP and their families.…”
Section: Discussioncontrasting
confidence: 89%
“…Therefore, it is important to broaden our understanding of the influence of demographics, referral process, and symptom improvements on case closure. Evidence that non mutual case closure may not necessarily be a problem may reflect more self-efficacy, competence, self-rated improvement, and autonomy among YP and their carers (Simon et al, 2012 ; O'Keeffe et al, 2019b ). Despite this wealth of knowledge, we are yet to fully understand if symptom improvement is an indicator of a “good” outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 28–75% of young clients quit treatment prematurely ( Swift and Greenberg, 2012 ). Their reasons are diverse: Some are dissatisfied, some perceive (whether or not the therapist concurs) that they have achieved what they wanted, and some quit because of difficulties outside therapy ( O’Keeffe et al, 2019 ). In-session events and therapist behaviors are linked to adolescents dropping out of treatment ( O’Keeffe et al, 2020 ), but it has been difficult to predict which young people are at risk of dropping out ( de Haan et al, 2013 ; O’Keeffe et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, children and young people frequently report being left out of conversations during appointments (Edbrooke‐Childs, Calderon, Wolpert, & Fonagy, 2015; Hayes, Edbrooke‐Childs, Town, Wolpert, & Midgley, 2019). This can result in an increased risk of drop out as the patient does not feel comfortable talking to the clinician, as well as not liking the structure and activity of the prescribed therapeutic modality (O’Keeffe, Martin, Target, & Midgley, 2019).…”
Section: Discussionmentioning
confidence: 99%